Structure of the Russian Internet-Community According to the Motives and Types of Civil Activity - Троцук, Ирина Владимировна; Савельева, Евгения Александровна (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
Today in the sociological discipline, there is an impressive collection of empirical data and conceptual approaches to the study of civil society as a complex and ambiguous phenomenon, including a set of empirical indicators for assessing its development, strength, and sustainability. However, the authors believe that this impressive collection of theoretical models and empirical findings still does not explain a specific phenomenon, which is very important for the Russian society – various formats of civil activism that are not always permanent or widespread, and, thus, ignored by the researchers. The article provides a model for conceptualization and empirical study of civil activism that aims to fill this gap and was tested in the online survey. The questionnaire of the online survey provides the criteria for structuring the Internet community according to the involvement in civil activity, and allows identifying its key motives and barriers. The results of the online survey, in particular, present seven types of Internet users according to different formats of civil activism: super-activists, volunteers, online activists, members of public organizations, passive observers, only voting in the elections, and outsiders.